2001
DOI: 10.1006/viro.2000.0737
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Three HERV-H Proviruses with an Open Envelope Reading Frame Encompassing the Immunosuppressive Domain and Evolutionary History in Primates

Abstract: The HERV-H family is one of the largest human endogenous retrovirus families, with approximately 1000 elements. Using a direct coupled in vitro transcription/translation approach (PTT for protein truncation test) and an extended series of primers on human genomic DNA, on monochromosomal hybrids and on a BAC library, we could demonstrate that there are only three envelopes with a large open reading frame encompassing the immunosuppressive (ISU) domain, corresponding to 62-, 60-, and 59-kDa potential translation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 35 publications
3
54
0
Order By: Relevance
“…The 59 end of this gene contains a 270 nucleotide Alu element. The sequence of this Alu element is identical to the human endogenous retrovirus family (HERV) Alu element [24,25], which is located toward the 59 end of HERV-H/env60 pol gene [24] and toward the leader region of the HERV-K family [25]. Thus, it is likely that the 59 Alu segment is a functional element that can drive the pseudogene expression in adult tissues or cultured cells as shown in other reports [26].…”
Section: Discussionmentioning
confidence: 82%
“…The 59 end of this gene contains a 270 nucleotide Alu element. The sequence of this Alu element is identical to the human endogenous retrovirus family (HERV) Alu element [24,25], which is located toward the 59 end of HERV-H/env60 pol gene [24] and toward the leader region of the HERV-K family [25]. Thus, it is likely that the 59 Alu segment is a functional element that can drive the pseudogene expression in adult tissues or cultured cells as shown in other reports [26].…”
Section: Discussionmentioning
confidence: 82%
“…It has been reported that the LTR of the HERV-H family contains potential binding sites for several kinds of transcriptional factors such as Sp1, HNF-1/Cdx, and CCAAT elements (Feuchter and Mager, 1990;Nelson et al, 1996;de Parseval et al, 2001). The HERV-H eleEdited by Norihiro Okadaments are strongly expressed in testicular and lung tumors (Wilkinson et al, 1990;Hirose et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…At least 22 distinct HERV families were identified in the human genome (Tristem 2000). HERVs are present in full-length or incomplete sequences with multiple stop codons, insertions, deletions, and frame shifts in them (Lee et al 2000;de Parseval et al 2001). However, structural genes from some HERV families are expressed preferentially in human placenta (Venables et al 1995) and several cancer cell lines (Lower et al 1993;Armbruester et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The HERV-H was inserted into primate genomes before the divergence of New World and Old World monkeys, and the elements lacking in pol and env were integrated with the Old World monkey lineage (Goodchild et al 1993;Anderssen et al 1997;de Parseval et al 2001). The full-length HERV-H env contains a region encoding an amino acid sequence highly similar to the immunosuppressive peptide in murine leukaemia virus (MLV) p15E protein that may suppress maternal immunological rejection of the fetus and may also be involved in tumor development (Cianciolo et al 1984(Cianciolo et al , 1985.…”
Section: Introductionmentioning
confidence: 99%